Acute kidney injury due to multiple wasp stings: a case report - Tahmina Khandkar; Amina Akter; Asaduzzaman Asaduzzaman; Ranjit Ranjan Roy; Golam Muinuddin (Paediatrica Indonesiana, 2021)
The skin is the most commonly affected organ. Wasp venom causes both local and systemic reactions, but acute kidney injury (AKI) is the most serious complication, with a 20% mortality rate. Acute kidney injury can occur from single or multiple stings. Diagnosis depends on history, clinical findings, and investigations. Treatment protocol is same as other causes of AKI, including dialysis, and prognosis is good with early treatment.